Republic of Kosovo : 2018 Article IV Consultation-Press Release; and Staff Report. (IMF Staff Country Reports; Country Report, 2018)
The near-term outlook is broadly positive, with robust growth and low inflation. However, growth potential remains constrained by weak external competitiveness, high informality, low labor force participation, and a large infrastructure gap. In a complex political environment, the structural reform progress has been slow and fiscal risks have increased.